2014
DOI: 10.1002/adma.201400883
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Material System Exhibiting Superwettability

Abstract: Engineering the wettability of solid materials is a traditional, yet key issue in surface science and attracts tremendous interest by researchers in diverse fields. Recently, different superwetting phenomena have been discovered in both nature and experimental results. Therefore, in this review, various superwetting states, leading to a "superwettability" system, are summarized and predicted. Fundamental rules for understanding superwettability are discussed, mainly taking superhydrophobicity in air as an exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
356
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 472 publications
(359 citation statements)
references
References 190 publications
(240 reference statements)
1
356
0
2
Order By: Relevance
“…[46] In the past two decades, there have been great breakthroughs in research into bionic superwettable surfaces, leading to promising solutions to issues arising in daily life and industry. [15][16][17][18][19][47][48][49] Herein, we show biological inspirations that guide the design and creation of CMDSP surfaces that own the remarkable self-removal ability of small-scale condensate microdrops. Gao et al [5] first reported that closely packed nanocones on the surface of mosquito eyes are fully nonsticky to condensed microdrops (Figure 1c-e), showing a dry-style antifogging function.…”
Section: Biological Prototypes Of Cmdsp Surfacesmentioning
confidence: 98%
See 1 more Smart Citation
“…[46] In the past two decades, there have been great breakthroughs in research into bionic superwettable surfaces, leading to promising solutions to issues arising in daily life and industry. [15][16][17][18][19][47][48][49] Herein, we show biological inspirations that guide the design and creation of CMDSP surfaces that own the remarkable self-removal ability of small-scale condensate microdrops. Gao et al [5] first reported that closely packed nanocones on the surface of mosquito eyes are fully nonsticky to condensed microdrops (Figure 1c-e), showing a dry-style antifogging function.…”
Section: Biological Prototypes Of Cmdsp Surfacesmentioning
confidence: 98%
“…Efforts in the past decades have explored controllable fabrication, functionality, and performance optimization of bionic superhydrophobic surfaces with a contact angle above 150°, and they have resulted in technological innovations such as self-cleaning, drag-reduction, anticorrosion, antifogging, antifreezing and oil-water separation. [15][16][17][18][19] Recently, intensive www.advmat.de www.advancedsciencenews.com demonstration of their technological potential for enhancement of heat transfer, [20][21][22][23][24][25] energy saving, [26][27][28] and electrostatic energy harvesting. [29] Currently, this multidisciplinary research direction, which includes biology, chemistry, physics, materials science, and engineering, is still in its infancy, but it has exhibited significance and vigor in both fundamental and technological aspects.…”
Section: Introductionmentioning
confidence: 99%
“…30-nm TiO 2 nanoparticles with mean were provided by Cinkarna Celje, whereas the 30-nm SiO 2 Steel substrate preparation. Prior to the application of the coating, the steel discs of 25 mm diameter and with a thickness of 1.5 mm were diamond polished following a standard mechanical procedure and then cleaned with ethanol in an ultrasonic bath.…”
Section: Experimental Partmentioning
confidence: 99%
“…Designing a solid surface with specific surface characteristics, such as wetting properties, mechanical resistance, anticorrosion properties, etc., is challenging in several applications in aerospace, marine, biomedicine etc 1,2 . Therefore, the surface modification of engineering metallic materials, such as the most commonly used austenitic stainless steel (AISI), 3,4 by various coatings represents an important subject in the field of enhancing particular surface properties, mechanical as well as anticorrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The liquid-wetting behavior on a solid or liquid surface is mainly dependent on the chemical composition and surface roughness, which play important roles in liquid transport. [9][10][11][12][13][14][15][16] The wettability gradient of a surface for a liquid droplet with an asymmetrical contact angle (CA) can produce a driving force for liquid motion, which is generally generated by introducing a chemical or structure gradient.…”
Section: Introductionmentioning
confidence: 99%